2009
DOI: 10.5380/rf.v39i1.13732
|View full text |Cite
|
Sign up to set email alerts
|

Fluxo De Nutrientes Pela Precipitação Pluviométrica Em Dois Trechos De Floresta Ombrófila Densa Em Guaraqueçaba, Paraná

Abstract: ResumoEste trabalho teve o objetivo de avaliar os fluxos de K, Ca, Mg e Na através da precipitação no exterior e no interior de dois trechos de Floresta Ombrófila Densa (capoeira: estágio inicial/intermediário de sucessão secundária de floresta aluvial e floresta secundária submontana), na Reserva Natural Salto Morato, em Guaraqueçaba, Paraná. A capoeira e a floresta secundária apresentaram valores de interceptação da água da chuva em torno de 14%, sendo baixos comparados com outros da literatura. As estimativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 22 publications
(37 reference statements)
1
17
0
10
Order By: Relevance
“…In the case of nonnative pine and eucalyptus forests, throughfall rates are usually higher in hardwood stands than in softwood stands (LIMA, 1976). Scheer (2009) studied the contribution of rainfall to nutrient flow in rain forests and noted that, by dragging the nutrients suspended in the atmosphere and subsequently washing them away from the surface of the leaves, rain precipitation plays an important part in returning such nutrients to the forest floor. The author observed that 65%, 15% and 5% of the flows of, respectively, potassium (K), magnesium (Mg) and calcium (Ca) to the forest floor was effected by throughfall.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of nonnative pine and eucalyptus forests, throughfall rates are usually higher in hardwood stands than in softwood stands (LIMA, 1976). Scheer (2009) studied the contribution of rainfall to nutrient flow in rain forests and noted that, by dragging the nutrients suspended in the atmosphere and subsequently washing them away from the surface of the leaves, rain precipitation plays an important part in returning such nutrients to the forest floor. The author observed that 65%, 15% and 5% of the flows of, respectively, potassium (K), magnesium (Mg) and calcium (Ca) to the forest floor was effected by throughfall.…”
Section: Introductionmentioning
confidence: 99%
“…Mean monthly rainfall was also measured in the study area using six 12.5 cm diameter, polyethylene funnels connected into fi ve liter polyethylene bottles. Each apparatus was mounted in a PVC tube so that each funnel rim was around 1 m above the soil surface (Scheer 2009). Rainfall was measured every two weeks corresponding to the same interval of litterfall collection.…”
Section: Methodsmentioning
confidence: 99%
“…Existing nutrients in a forest ecosystem originate from two main natural sources: the weathering process and additions by rainfall. Maintenance of productivity over successive crop rotations depends on the speed with which new nutrients are released by weathering, addition through rainfall or artificial addition through fertilization (SCHRUMPF et al 2006).…”
Section: Calil F N Et Almentioning
confidence: 99%
“…The key role played by water in the current geopolitical context has prompted research studies to try and preserve water quality, improve its use and application conditions, and analyze its chemical composition in a given system. Rainfall, also known as wet precipitation, is a natural atmosphere cleansing process that draws existing chemical elements and compounds and deposits them on the earth's surface (SCHEER 2009). Atmospheric composition is influenced both by natural and anthropogenic sources, and results from the incorporation of particles and gases into water droplets (PANETTIERE et al 2000).…”
Section: Introductionmentioning
confidence: 99%